Methodological features of elaborating and implementing bioeconomy development strategy in a region - Павліха, Наталія Володимирівна; Кицюк, Ірина Василівна; Pavlikha, Nataliia V.; Kytsiuk, Iryna V. (The Publishing House of the Pope John Paul II State School of Higher Education in Biała Podlaska, Poland, 2015)
This paper aims to consider the methodological features of elaborating and implementing bioeconomy development strategy in a region. The basis for discussion is a critical literature review. Nowadays the international community pays much attention to the sustainable spatial development. In our opinion one of the effective factors of sustainable spatial development is a bioeconomy. The mission of a bioeconomy as effective condition for sustainable development is a process of survival and reproduction of the gene pool of population, activation of the role of each individual person in a society, ensuring their rights and freedoms, saving the environment, creating conditions for the restoration of the biosphere and its local ecosystems, orientation on the reduction of the human impacts on environment and harmonization of man development in nature. We emphasize that the system and network planning methodology, which is in the base of the project management theory, must be used for elaborating and implementing bioeconomy development strategy in a region. Thus, the concept of project management exactly conforms to the complexity and dynamicity of the processes of bioeconomy development in a region. The methodology expects the activity of economic entities as to the spatial concretization and implementing of the strategy of balanced socio-economic and Eco Safety development of a region. To our mind, it is necessary consistently and purposefully to realize the innovations in the bioeconomy. We pay attention to the Eco Safety Innovations.
Aspekty metodologiczne opracowania i wdrażania strategii rozwoju bioekonomii w regionie
Keywords: Sustainable Spatial Development; Bioeconomy; Project Management; Eco Safety Innovations